A Novel Fuzzy Logic EMS for Hybrid Microgrids with Photovoltaic, Wind, Fuel Cell, and Energy Storage Integration - Kabouri Omar; Azeroual Mohamed; El Markhi Hassane; Bagayogo Alhussien (E3S Web of Conferences)
This paper presents an innovative Energy Management Strategy (EMS) for a hybrid microgrid that combines two main renewable energy sources (RESs), photovoltaic (PV) and wind turbine (WT) generators working at the maximum power point (MPP) to extract the maximum available energy, and an energy storage system (ESS) based Lithium batteries to ensure DC-bus stability. This system includes a backup device based on Fuel Cell (FC) to assure system dependability and minimize blackouts, as well as power electronic converters for flexible system parts and a residential community as DC loads. The proposed EMS is based on the advanced Fuzzy Logic Controller (FLC), which regulates voltage and manages power flow inside the microgrid. MATLAB/Simulink simulations were conducted to assess the performance of innovative microgrid stability strategy. A comparative analysis with conventional EMS approaches demonstrates the superior effectiveness and viability of the proposed FLC technique in energy management within microgrids. The simulation-based comparison indicates that the proposed optimization method enhances system performance and DC-bus stability.